Clinical features and management of atypical hemolytic uremic syndrome patient with DGKE gene variants: a case report - Dai, Xiaomei; Ma, Yu; Lin, Qiang; Tang, Hanyun; Chen, Ruyue; Zhu, Yun; Shen, Yunyan; Cui, Ningxun; Hong, Zhongqin; Li, Yanhong; Li, Xiaozhong (Frontiers in Pediatrics, 2023)
Background: Atypical hemolytic uremic syndrome (aHUS) with diacylglycerol kinase epsilon (DGKE) gene variant is a rare variant of thrombotic microangiopathy (TMA). The information on the clinical features, management and long-term outcomes of DGKE-aHUS patients have not yet been fully elucidated. The aim of this study was to report a novel variant of the DGKE gene in a Chinese population with aHUS. Case presentation: The present work reports a 7-month-old boy with aHUS, possibly triggered by gastrointestinal infection, without complement activation, with little response to plasma therapy and nephroprotective measures. The patient died during the 8th week of his hospital stay. The causes of death were intracranial hemorrhage and multiorgan dysfunction. Comprehensive WES of peripheral blood-derived DNA revealed two heterozygous variations in the DGKE exon region: NM_003647.2, c.610dup, p.Thr204Asnfs*4 and deletion of exons 4-6. Conclusions: This case suggest that atypical HUS with DGKE gene variant has a poor prognosis with a high mortality rate, which typically manifests in the first year of life and presents as a systemic disease with early-onset HUS with rapidly worsening renal function and chronic proteinuria. There is no specific treatment for DGKE-aHUS. There have an uncertain benefit of plasma therapy for DGKE-aHUS patients. The literature demonstrated that anti-complement therapy showed benefits for DGKE-aHUS with complement activation and autoantibodies during the overt TMA presentation but did not prevent TMA relapses. Early diagnosis and treatment may prevent complications and improve prognosis.